Characterization of a Compton camera based on the TOFPET2 ASIC. (January 2023) - Viegas, R.; Roser, J.; Barrientos, L.; Borja-Lloret, M.; Casaña, J.V.; López, J. García; Jiménez-Ramos, M.C.; Hueso-González, F.; Ros, A.; Llosá, G.
Abstract: The use of Compton cameras for medical imaging and its interest as a hadron therapy treatment monitoring has increased in the last decade with the development of silicon photomultipliers. MACACO p is a Compton camera prototype designed and assembled at the IRIS group of IFIC-Valencia. This Compton camera is based on monolithic Lanthanum (III) Bromide crystals and silicon photomultipliers, and employs the novel TOFPET2 ASIC as readout electronics. This system emerged as an alternative to MACACO II prototype, with the aim of improving its limited time resolution. To test the performance of the ASIC in a Compton camera setup, the prototype was characterized, both in laboratory and in-beam. A time resolution of 1.5 ns was obtained after time corrections, which improves greatly the performance of the MACACO II. Moreover, the results obtained at high photon energies demonstrate the ability of the system to obtain 1 mm displacements of the reconstructed spots. The results reinforce the potential of the system as a monitoring device for hadron therapy. Highlights: Compton camera, MACACOp, characterized and developed for hadron therapy monitoring. Two layer Compton camera based on monolithic LaBr3 and Silicon photomultipliers. TOFPET2 ASIC as readout electronics to improve Compton camera's time resolution. Timing resolution close to 1 ns FWHM obtained with Compton camera. Compton camera able to distinguish 1 mm range shifts at high photon energies.